DAMPAK KELOMPOK SEL BAGI PERTUMBUHAN GEREJA - Dully, Stefanus (Voice of HAMI: Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
A cell group is a group of people who live together in an area, or who have the same interests, or under one rule of law. Cell group is a collection of people who live close to each other and have social relations, or common ownership, or share with each other. The application of cell groups certainly has an impact on creating church growth both in quality and in terms of quantity. The article entitled The Impact of Cell Groups on Church Growth describes how cell groups their selves. The method used in writing this article is a qualitative descriptive method. The description on this topic, when traced to the cell group in the Old and New Testaments is supported by its application.The goal of implementing cell groups is to avoid stagnation in service. Cell groups are also closely related in the ministry of deacons, koinonia, marturia and didaskalia. By implementing cell groups it creates growth for the church through increasing the number and increasing the quality of faith. Keywords: Cell Groups, Church Growth, Believers ABSTRAK Kelompok sel adalah sekelompok orang yang hidup bersama-sama disuatu area, atau yang memiliki ketertarikan yang sama, atau dibawah satu peraturan hukum. Komsel adalah suatu kumpulan orang yang hidup saling berdekatan dan memiliki hubungan sosial, atau kepemilikan bersama, atau saling berbagi. Penerapan kelompok sel tentu berdampak untuk menciptakan pertumbuhan gereja baik secara kualitas maupun secara kuntittas. Tulisan yang berjudul Dampak Kelompok Sel Bagi Pertumbuhan Gereja menguraikan bagaimana kelompol sel itu sendiri. Metode yang digunakan dalam penulisan artikel ini adalah metode deskriftif kualitatif. Uraian pada topik ini, kelompok sel itu bila dilitesuri dalam Perjanjian Lama dan Perjanjian Baru didukung penerapannya. Tujaun dari penerapan kelompok sel untuk menghindari stagnasi dalam pelayanan. Kelompok sel juga erat kaitannya dalam pelayanan diakonia, koinonia, marturia dan didaskalia. Dengan menerapkan kelompok sel menciptakan pertumbuhan bagi gereja. Kata-Kunci: Kelompok Sel, Pertumbuhan Gereja, Orang Percaya